2006
DOI: 10.1002/cne.21027
|View full text |Cite
|
Sign up to set email alerts
|

Netrin/DCC‐mediated attraction of vagal sensory axons to the fetal mouse gut

Abstract: Vagal sensory axons and migrating neural crest-derived precursor cells follow similar pathways to reach the gut. The crest-derived cells express the netrin receptor deleted in colorectal cancer (DCC) and migrate toward netrins expressed by the intestinal mucosa and pancreas; this attraction is required for the formation of submucosal and pancreatic ganglia. We tested the hypothesis that enteric netrins also attract vagal sensory fibers. These axons were located as a function of age in fetal mice by applying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
89
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(97 citation statements)
references
References 49 publications
8
89
0
Order By: Relevance
“…Research in the late 1980s and 1990s revealed that vagal axons first enter the mouse stomach at E11 (Baetge and Gershon, 1989), the rat stomach at E12 (Rinaman and Levitt, 1993), and were present in the mouse esophagus at E12 (Sang and Young, 1998). These observations were extended by studies in which the liphophilic dye, 1,1′-dioctadecyl-3,3,3′, 3′-tetramethylindocarbocyanine perchlorate (DiI) was applied to the nodose ganglia of embryonic day (E) 12, E14 and E16 fetal mice (Ratcliffe et al, 2006). This work showed that the stomach receives vagal sensory fibers by E12 and that the celiac ganglion and duodenum are innervated by E14.…”
Section: Molecular Development Of Enteric Vagal Afferentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Research in the late 1980s and 1990s revealed that vagal axons first enter the mouse stomach at E11 (Baetge and Gershon, 1989), the rat stomach at E12 (Rinaman and Levitt, 1993), and were present in the mouse esophagus at E12 (Sang and Young, 1998). These observations were extended by studies in which the liphophilic dye, 1,1′-dioctadecyl-3,3,3′, 3′-tetramethylindocarbocyanine perchlorate (DiI) was applied to the nodose ganglia of embryonic day (E) 12, E14 and E16 fetal mice (Ratcliffe et al, 2006). This work showed that the stomach receives vagal sensory fibers by E12 and that the celiac ganglion and duodenum are innervated by E14.…”
Section: Molecular Development Of Enteric Vagal Afferentsmentioning
confidence: 99%
“…This work showed that the stomach receives vagal sensory fibers by E12 and that the celiac ganglion and duodenum are innervated by E14. DiI-labeled vagal axons reach the distal small intestine by E16 and, at the same stage, form a plexus in the esophageal musculature (Ratcliffe et al, 2006). Vagal terminals in the developing mouse stomach were also recently characterized using DiI (Murphy and Fox, 2007).…”
Section: Molecular Development Of Enteric Vagal Afferentsmentioning
confidence: 99%
See 3 more Smart Citations